Influence of micro jets on wall pressure for area ratio 3.24 - Ashfaq, Syed; Khan, Sher Afghan (International Journal of Emerging Technology and Advanced Engineering (IJETAE), 2014)
In this paper results of experimental studies conducted to study the development of flow from a convergent nozzle in to a suddenly expanded duct and also to quantify the effect of micro jets, on the duct flow field presented. The parameters considered in the present studies are the length to diameter ratio, Mach number and area ratio. The Mach numbers considered are 0.6, 0.8 and 0.9, respectively. The area ratio (ratio of area of suddenly expanded duct to nozzle exit area) studied is 3.24. The length-to-diameter (L/D) ratio of the sudden expansion duct was varied from 10 to 1. To quantify the quality of flow in the enlarged duct wall pressure was measured and it is found that the flow field remains the same with and without control. However, oscillations are observed for L/Ds = 10, 8, 6, and 5 for all the Mach numbers which has shown that even for correctly expanded flow the flow is wave dominated.